A low-density, high-conductivity copper-clad magnesium conductor and a preparation method thereof
Through friction stir welding and rare earth element addition, the problem of magnesium alloy core melting when copper-clad magnesium alloy wires is connected is solved, and the conductivity and strength are improved through low-temperature aging treatment, achieving low-density, high conductivity and excellent mechanical properties of copper-clad magnesium conductors.
Patent Information
- Application Number
- CN202411579177.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing connection methods of copper-clad magnesium alloy wires are likely to cause melting of the magnesium alloy core, causing uneven microstructure and pose safety hazards; their conductivity and mechanical properties are low, and the line break rate during the drawing process is high.
The copper layer is welded on the magnesium alloy core by friction stir welding to avoid melting of the magnesium alloy; rare earth elements are added to the magnesium alloy core to reduce the content of impurities and improve the plasticity of the magnesium alloy; nanoclusters are formed through low-temperature and short-term aging treatment after drawing, and conductivity and strength are improved.
The low density, high conductivity and excellent mechanical properties of copper-clad magnesium conductors are achieved, reducing safety hazards and line breakage rates in the production process.
Smart Images

Figure BDA0005122579250000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable and conductor production, and in particular to a low-density and high-conductivity copper-clad magnesium conductor and a preparation method thereof. Background Art
[0002] Conductive wires are widely used in new energy vehicles, aerospace, low-altitude economic equipment and 3C electronic products. Currently, the commonly used alloy wires are mainly copper alloy wires and aluminum alloy wires. Compared with copper alloy wires, aluminum alloy wires have lower conductivity, about 60% IACS. Copper alloys have high conductivity, however, copper alloys have high density and high prices. With the development of new energy vehicles and low-altitude economic equipment, conductive wires are required to have low density, low cost, high conductivity and excellent mechanical properties. The density of magnesium alloy is 1.8g / cm 3 , its density is only about 2 / 3 of that of aluminum alloy, which is the lowest density structural metal. In addition, magnesium alloy also has excellent electromagnetic shielding performance. The preparation of copper-clad magnesium alloy composite wire by compounding copper and magnesium alloy materials is expected to significantly reduce its density. In addition, due to the excellent electromagnetic shielding performance of magnesium alloy, copper-clad magnesium alloy composite wire can be used in the braided layer of high-end cables to isolate the electromagnetic field of the wire inside the shielding layer from the electromagnetic field outside the shielding layer, thereby improving the stability of conductive signal transmission.
[0003] At present, relevant patents have proposed methods for preparing copper-clad magnesium alloy wires. However, copper-clad magnesium alloy wires and their preparation methods currently have the following three main problems. First, the connection method of copper-clad magnesium alloy composite wires can easily cause the magnesium alloy core to melt, resulting in uneven microstructure and prone to safety hazards. In the existing technology, argon arc welding is used to coat the copper layer on the outer layer of the magnesium alloy core. For example, in the current technology, application No. 202111322186.9 proposes to coat the copper layer on the surface of the magnesium alloy core through a composite device, and to perform argon arc welding on the copper-clad magnesium alloy composite wire to weld the copper layer on the surface of the magnesium alloy wire. There will be local melting during argon arc welding, and the local temperature can exceed 1000°C, which is much higher than the melting point of magnesium alloy, resulting in local melting of magnesium alloy wires, reducing the uniformity of material organization, and increasing the wire breakage rate. In addition, since magnesium alloys are easy to burn after melting, melting welding represented by argon arc welding will increase safety hazards in the production process. Second, the electrical conductivity and mechanical properties of copper-clad magnesium alloy composite wires are low, and the wire breakage rate is high during drawing. This is related to the copper layer and magnesium alloy core composition and drawing process of the copper-clad magnesium alloy composite wire. The current technology application No. 201410598674.6 proposes a copper-clad magnesium alloy wire and a preparation method thereof. The magnesium alloy composition is as follows according to weight percentage: Al: 10-12%, Eu: 0.5-1.5%, Re: 0.2-0.6%, Ca: 1.2-1.6%, Th: 0.5-1.5%, Nd: 2.1-2.3%, Co: 0.7-1.3%, Ta: 0.8-1.0%, Dy: 0.05-0.15%, W: 0.2-0.4%, Rh: 0.7-0.9%, Sb: 2.1-2.3%, Bi: 2.1-2.3%, Ho: 0.3-0.5%, and the balance is Mg. In this patent application, the alloying element content of the magnesium alloy core exceeds 20% by weight. The use of a large amount of alloying elements will increase the material cost. In addition, the magnesium alloy core with high alloying element content has poor plasticity and is prone to breakage during the drawing process, increasing the wire breakage rate. Therefore, it is urgent to find a low-density, high-conductivity copper-clad magnesium conductor and its preparation method, which can improve the conductivity and strength of the conductor and reduce the wire breakage rate during the drawing process while ensuring the low density of the copper-clad magnesium conductor. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a low-density and high-conductivity copper-clad magnesium conductor and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A low-density high-conductivity copper-clad magnesium conductor comprises a magnesium alloy core and a copper layer, wherein the copper layer covers the surface of the magnesium alloy core, wherein the magnesium alloy core contains, by weight percentage, 0.5%-3% rare earth elements, the remainder being Mg and inevitable impurity elements, and the copper layer contains, by weight percentage, 0.2%-0.5% Mg, the remainder being Cu and inevitable impurity elements.
[0007] Preferably, the rare earth element is one of lanthanum, cerium, neodymium, samarium, gadolinium or erbium, scandium, yttrium; to ensure the uniformity of deformation of the magnesium alloy core during the drawing process, the content of the rare earth element is less than its maximum solid solubility to avoid the precipitation of the second phase.
[0008] A method for preparing a low-density and high-conductivity copper-clad magnesium conductor comprises the following steps:
[0009] Step 1, preparing a magnesium alloy block and a copper alloy block;
[0010] Putting pure magnesium ingots and Mg-Re master alloy into a smelting furnace according to weight percentage, smelting the magnesium alloy under the protection of SF6 gas, mechanically stirring for 3-5 minutes after complete smelting, slagging, adding refining agent to the magnesium alloy molten liquid after slagging, refining, and slagging again, casting the magnesium alloy after slagging to obtain a magnesium alloy block, and homogenizing the obtained magnesium alloy block;
[0011] Firstly, a pure copper block is put into a smelting furnace according to weight percentage, and a pure magnesium block is put into the smelting furnace after the copper block is completely melted, and then the magnesium block is cast after it is completely melted to obtain a copper alloy block, and the obtained copper alloy block is homogenized;
[0012] Step 2: Preparation and pretreatment of magnesium alloy core and copper strip;
[0013] Extruding the homogenized magnesium alloy block to obtain a magnesium alloy core, pre-treating the obtained magnesium alloy core to remove oil stains and oxides on the surface of the magnesium alloy core, and passivating the magnesium alloy core;
[0014] The copper alloy block after homogenization is rolled to obtain a copper strip, and the obtained copper strip is pretreated to remove oil and oxide on the surface of the copper strip, and the copper strip is passivated to increase the friction between the copper strip and the magnesium alloy core;
[0015] Step 3, welding the magnesium alloy core and the copper strip cladding;
[0016] The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device;
[0017] Then the magnesium alloy core uniformly coated with copper strips enters the welding area, and the copper-clad magnesium is welded by stir friction welding, and mechanically polished to make the surface smooth to obtain a copper-clad magnesium wire with a diameter of 4.5-7 mm;
[0018] Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
[0019] Preferably, in step 1, the magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 100-120 mm.
[0020] Preferably, in step 1, the temperature of the magnesium alloy block homogenization treatment is 450-500° C., the time is 8-12 hours, and the magnesium alloy block after homogenization is surface treated to remove the surface oxide of the magnesium alloy block.
[0021] Preferably, in step 2, the magnesium alloy block is extruded at a temperature of 400° C.-450° C. and is extruded into a round rod with a diameter of 4-6 mm.
[0022] Preferably, in step 1, the homogenization temperature of the copper alloy block is 850° C.-900° C., and the homogenization time is 6-10 hours.
[0023] Preferably, in step 2, the copper alloy block rolling process is as follows: the copper alloy block after homogenization is hot rolled at 780°C from 30 mm to 15 mm, with a reduction of 20% per pass, the copper alloy block is hot rolled into a plate, and then the hot rolled plate is cold rolled from 15 mm to 2 mm, with a reduction of 15% per pass;
[0024] The cold rolled sheet is then heat treated at 430°C for 4-6 hours;
[0025] The plate is then cold rolled from 2 mm to 0.5-1 mm, with a reduction of 10% per pass;
[0026] After cold rolling, the plate is heat treated at 320°C for 4-6 hours.
[0027] Preferably, in step 3, during the friction stir welding process, the rotation speed of the stirring head is 1000 rpm, the foreground speed of the stirring head is 3-12 m / min, and the length of the stirring needle is the same as the thickness of the clad copper layer: 0.5-1 mm.
[0028] Preferably, in step 4, the copper-clad magnesium wire obtained in step 3 is subjected to a first continuous drawing, the wire diameter after the first continuous drawing is 2-3 mm, and a vacuum annealing furnace is carried out after continuous drawing, the temperature in the furnace is set to 400° C.-500° C., and the insulation time is 30 seconds-50 seconds;
[0029] The annealed copper-clad magnesium wire is subjected to a second continuous drawing, and the diameter of the copper-clad magnesium wire after the second continuous drawing is 0.8-1mm. After continuous drawing, it is placed in a vacuum annealing furnace, and the temperature in the furnace is set to 400℃-500℃, and the insulation time is 30 seconds-50 seconds;
[0030] The annealed copper-clad magnesium wire is continuously drawn for the third time, and the diameter of the copper-clad magnesium wire after the third continuous drawing is 0.2-0.3 mm. After continuous drawing, it is placed in a vacuum annealing furnace, and the temperature in the furnace is set to 400°C-500°C, and the insulation time is 30 seconds-50 seconds;
[0031] The annealed copper-clad magnesium wire is drawn for the fourth time, and the diameter of the copper-clad magnesium wire after the fourth drawing is 0.08-0.1 mm. After the drawing, it is put into a vacuum annealing furnace, the temperature in the furnace is set to 180°C-210°C, the insulation time is 60 seconds-120 seconds, and the copper-clad magnesium wire is cooled to room temperature to obtain the copper-clad magnesium wire.
[0032] The beneficial effects of the present invention are:
[0033] 1. In the present invention, the friction stir welding method is used to achieve the welding of the copper layer. Since friction stir welding is a solid-state bonding process, there is no melting of the copper layer. While ensuring the mechanical properties of the copper layer, the risk of magnesium alloy combustion in the production process is reduced.
[0034] 2. In the present invention, a low alloy content magnesium alloy Mg-Re alloy is selected, and the Re content should be lower than the maximum solid solubility of the rare earth element in the magnesium alloy to avoid the precipitation of the second phase, resulting in uneven organization and increased wire breakage rate; the outer copper layer can be selected from Cu-Mg and Cu-Ag alloys to improve its strength.
[0035] 3. In the present invention, a low-temperature short-time aging treatment is adopted after drawing, so that the solute atoms are segregated at the defects during the aging process to form nanoclusters, which reduces the decrease in conductivity caused by phonon scattering by alloy atoms and improves its strength and plasticity. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0037] A low-density high-conductivity copper-clad magnesium conductor comprises a magnesium alloy core and a copper layer, wherein the copper layer covers the surface of the magnesium alloy core, wherein the magnesium alloy core contains 0.5%-3% rare earth elements by weight, and the balance is Mg and inevitable impurity elements, and the copper layer contains 0.2%-0.5% Mg by weight, and the balance is Cu and inevitable impurity elements.
[0038] The rare earth element is one of lanthanum, cerium, neodymium, samarium and gadolinium or erbium, scandium and yttrium; in order to ensure the uniformity of deformation of the magnesium alloy core during the drawing process, the content of the rare earth element is less than its maximum solid solubility to avoid the precipitation of the second phase;
[0039] The purpose of adding rare earth elements is to purify the magnesium alloy melt, promote the initiation of non-basal slip during drawing, and reduce the wire breakage rate of the magnesium alloy core during drawing. Therefore, the rare earth element content should be higher than 0.5wt% by weight. Because the addition of excessive rare earth elements is difficult to further improve the wire breakage rate, the rare earth element content is less than 3wt% by weight.
[0040] Embodiment 1, a method for preparing a low-density and high-conductivity copper-clad magnesium conductor, comprising the following steps:
[0041] Step 1, preparing a magnesium alloy block and a copper alloy block;
[0042] The magnesium alloy block contains the following components by weight percentage: rare earth element Y: 3%, the balance being Mg and inevitable impurity elements. Pure magnesium ingots and Mg-Y master alloys are placed in a smelting furnace by weight percentage, and the magnesium alloy is smelted under the protection of SF6 gas. After complete smelting, mechanical stirring is performed for 5 minutes, and slag is removed. A refining agent is added to the magnesium alloy molten liquid after slag removal for refining, and slag is removed again. After slag removal, the magnesium alloy is cast to obtain a magnesium alloy block. The magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 110 mm, and the obtained magnesium alloy block is homogenized. The temperature of the magnesium alloy block homogenization treatment is 450° C., and the time is 12 hours. The magnesium alloy block after homogenization needs to be surface treated to remove surface oxides.
[0043] The copper layer composition contains Mg: 0.2% by weight, and the balance is Cu and inevitable impurity elements. A pure copper block is first placed in a smelting furnace by weight, and a pure magnesium block is placed after the copper block is completely melted. After the magnesium block is completely melted, it is cast to obtain a copper alloy block, and the obtained copper alloy block is homogenized; the homogenization temperature of the copper alloy block is 850° C., and the homogenization time is 10 hours;
[0044] Step 2: Preparation and pretreatment of magnesium alloy core and copper strip;
[0045] The magnesium alloy block after homogenization is extruded to obtain a magnesium alloy core. The magnesium alloy block is extruded at a temperature of 450° C. into a round rod with a diameter of 6 mm. The obtained magnesium alloy core is pretreated to remove surface oil and oxides, and is passivated.
[0046] The copper alloy block after homogenization treatment is rolled, and the rolling process of the copper alloy block is as follows: the copper alloy block after homogenization treatment is hot rolled at 780°C, the copper alloy block is hot rolled into a plate, the hot rolling is from 30mm to 15mm, and the reduction amount for each pass is 20%, and then the hot-rolled plate is cold rolled from 15mm to 2mm, and the reduction amount for each pass is 15%; then the cold-rolled plate is heat-treated at 430°C for 4 hours; then the plate is cold-rolled from 2mm to 0.5mm, and the reduction amount for each pass is 10%; the cold-rolled plate is heat-treated at 320°C for 4 hours; a copper strip is obtained, and the obtained copper strip is pre-treated to remove surface oil and oxides, and passivation treatment is performed to increase the friction between the copper strip and the magnesium alloy core.
[0047] Step 3, welding the magnesium alloy core and the copper strip cladding;
[0048] The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device;
[0049] Then the magnesium alloy core uniformly coated with copper strip enters the welding area, and the copper-clad magnesium is welded by stir friction welding. During the stir friction welding process, the rotation speed of the stirring head is 1000rpm, the foreground speed of the stirring head is 6m / min, and the length of the stirring needle is the same as the thickness of the coated copper layer: 0.5mm; after welding, the surface is mechanically polished to make the surface smooth, and the copper-clad magnesium wire is obtained, and the diameter of the copper-clad magnesium wire is 7mm;
[0050] Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
[0051] The copper-clad magnesium wire obtained in step 3 is subjected to the first continuous drawing, and the wire diameter after the first continuous drawing is 3 mm. After drawing, it is subjected to a vacuum annealing furnace, and the temperature in the furnace is set to 500° C., and the insulation time is 50 seconds;
[0052] The annealed copper-clad magnesium wire is drawn for the second time. The diameter of the copper-clad magnesium wire after the second drawing is 0.8 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 500°C and the holding time is 50 seconds.
[0053] The annealed copper-clad magnesium wire is drawn for the third time. The diameter of the copper-clad magnesium wire after the third drawing is 0.2 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 400°C and the holding time is 30 seconds.
[0054] The annealed copper-clad magnesium wire was drawn for the fourth time. The diameter of the copper-clad magnesium wire after the fourth drawing was 0.08 mm. After drawing, it was put into a vacuum annealing furnace with the temperature in the furnace set to 180° C. for 120 seconds and cooled to room temperature to obtain the copper-clad magnesium wire.
[0055] Embodiment 2, a method for preparing a low-density and high-conductivity copper-clad magnesium conductor, comprising the following steps:
[0056] Step 1, preparing a magnesium alloy block and a copper alloy block;
[0057] The magnesium alloy block contains the following components by weight percentage: rare earth element Y: 3%, the balance being Mg and inevitable impurity elements. Pure magnesium ingots and Mg-Y master alloys are placed in a smelting furnace by weight percentage, and the magnesium alloy is smelted under the protection of SF6 gas. After complete smelting, mechanical stirring is performed for 5 minutes, and slag is removed. A refining agent is added to the magnesium alloy molten liquid after slag removal for refining, and slag is removed again. After slag removal, the magnesium alloy is cast to obtain a magnesium alloy block. The magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 110 mm, and the obtained magnesium alloy block is homogenized. The temperature of the magnesium alloy block homogenization treatment is 450° C., and the time is 12 hours. The magnesium alloy block after homogenization needs to be surface treated to remove surface oxides.
[0058] The copper layer composition contains Mg: 0.2% by weight, and the balance is Cu and inevitable impurity elements. A pure copper block is first placed in a smelting furnace by weight, and a pure magnesium block is placed after the copper block is completely melted. After the magnesium block is completely melted, it is cast to obtain a copper alloy block, and the obtained copper alloy block is homogenized; the homogenization temperature of the copper alloy block is 850° C., and the homogenization time is 10 hours;
[0059] Step 2: Preparation and pretreatment of magnesium alloy core and copper strip;
[0060] The magnesium alloy block after homogenization is extruded to obtain a magnesium alloy core. The magnesium alloy block is extruded at a temperature of 450° C. into a round rod with a diameter of 6 mm. The obtained magnesium alloy core is pretreated to remove surface oil and oxides, and is passivated.
[0061] The copper alloy block after homogenization treatment is rolled, and the rolling process of the copper alloy block is as follows: the copper alloy block after homogenization treatment is hot rolled at 780°C, the copper alloy block is hot rolled into a plate, the hot rolling is from 30mm to 15mm, and the reduction amount for each pass is 20%, and then the hot-rolled plate is cold rolled from 15mm to 2mm, and the reduction amount for each pass is 15%; then the cold-rolled plate is heat-treated at 430°C for 4 hours; then the plate is cold-rolled from 2mm to 1mm, and the reduction amount for each pass is 10%; the cold-rolled plate is heat-treated at 320°C for 4 hours; a copper strip is obtained, and the obtained copper strip is pre-treated to remove surface oil and oxides, and is passivated to increase the friction between the copper strip and the magnesium alloy core.
[0062] Step 3, welding the magnesium alloy core and the copper strip cladding;
[0063] The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device;
[0064] Then the magnesium alloy core uniformly coated with copper strip enters the welding area, and the copper-clad magnesium is welded by stir friction welding. During the stir friction welding process, the rotation speed of the stirring head is 1000rpm, the foreground speed of the stirring head is 6m / min, and the length of the stirring needle is the same as the thickness of the coated copper layer: 1mm; after welding, the surface is mechanically polished to make the surface smooth, and the copper-clad magnesium wire is obtained, and the diameter of the copper-clad magnesium wire is 8mm;
[0065] Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
[0066] The copper-clad magnesium wire obtained in step 3 is subjected to the first continuous drawing, and the wire diameter after the first continuous drawing is 3 mm. After drawing, it is subjected to a vacuum annealing furnace, and the temperature in the furnace is set to 500° C., and the insulation time is 50 seconds;
[0067] The annealed copper-clad magnesium wire is drawn for the second time. The diameter of the copper-clad magnesium wire after the second drawing is 0.8 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 500°C and the holding time is 50 seconds.
[0068] The annealed copper-clad magnesium wire is drawn for the third time. The diameter of the copper-clad magnesium wire after the third drawing is 0.2 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 400°C and the holding time is 30 seconds.
[0069] The annealed copper-clad magnesium wire was drawn for the fourth time. The diameter of the copper-clad magnesium wire after the fourth drawing was 0.08 mm. After drawing, it was put into a vacuum annealing furnace with the temperature in the furnace set to 180° C. for 120 seconds and cooled to room temperature to obtain the copper-clad magnesium wire.
[0070] Embodiment 3, a method for preparing a low-density and high-conductivity copper-clad magnesium conductor, comprising the following steps:
[0071] Step 1, preparing a magnesium alloy block and a copper alloy block;
[0072] The magnesium alloy block contains the following components by weight percentage: rare earth element Gd: 0.5%, and the balance is Mg and inevitable impurity elements. Pure magnesium ingots and Mg-Gd master alloys are placed in a smelting furnace by weight percentage, and the magnesium alloy is smelted under the protection of SF6 gas. After complete smelting, mechanical stirring is performed for 5 minutes, and slag is removed. A refining agent is added to the magnesium alloy molten liquid after slag removal for refining, and slag is removed again. After slag removal, the magnesium alloy is cast to obtain a magnesium alloy block. The magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 110 mm, and the obtained magnesium alloy block is homogenized. The temperature of the magnesium alloy block homogenization treatment is 450° C., and the time is 12 hours. The magnesium alloy block after homogenization needs to be surface treated to remove surface oxides.
[0073] The copper layer composition contains Mg: 0.2% by weight, and the balance is Cu and inevitable impurity elements. A pure copper block is first placed in a smelting furnace by weight, and a pure magnesium block is placed after the copper block is completely melted. After the magnesium block is completely melted, it is cast to obtain a copper alloy block, and the obtained copper alloy block is homogenized; the homogenization temperature of the copper alloy block is 850° C., and the homogenization time is 10 hours;
[0074] Step 2: Preparation and pretreatment of magnesium alloy core and copper strip;
[0075] The magnesium alloy block after homogenization is extruded to obtain a magnesium alloy core. The magnesium alloy block is extruded at a temperature of 450° C. into a round rod with a diameter of 6 mm. The obtained magnesium alloy core is pretreated to remove surface oil and oxides, and is passivated.
[0076] The copper alloy block after homogenization treatment is rolled, and the rolling process of the copper alloy block is as follows: the copper alloy block after homogenization treatment is hot rolled at 780°C, the copper alloy block is hot rolled into a plate, the hot rolling is from 30mm to 15mm, and the reduction amount for each pass is 20%, and then the hot-rolled plate is cold rolled from 15mm to 2mm, and the reduction amount for each pass is 15%; then the cold-rolled plate is heat-treated at 430°C for 4 hours; then the plate is cold-rolled from 2mm to 0.5mm, and the reduction amount for each pass is 10%; the cold-rolled plate is heat-treated at 320°C for 4 hours; a copper strip is obtained, and the obtained copper strip is pre-treated to remove surface oil and oxides, and passivation treatment is performed to increase the friction between the copper strip and the magnesium alloy core.
[0077] Step 3, welding the magnesium alloy core and the copper strip cladding;
[0078] The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device;
[0079] Then the magnesium alloy core uniformly coated with copper strip enters the welding area, and the copper-clad magnesium is welded by stir friction welding. During the stir friction welding process, the rotation speed of the stirring head is 1000rpm, the foreground speed of the stirring head is 6m / min, and the length of the stirring needle is the same as the thickness of the coated copper layer: 0.5mm; after welding, the surface is mechanically polished to make the surface smooth, and the copper-clad magnesium wire is obtained, and the diameter of the copper-clad magnesium wire is 7mm;
[0080] Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
[0081] The copper-clad magnesium wire obtained in step 3 is subjected to the first continuous drawing, and the wire diameter after the first continuous drawing is 3 mm. After drawing, it is subjected to a vacuum annealing furnace, and the temperature in the furnace is set to 500° C., and the insulation time is 50 seconds;
[0082] The annealed copper-clad magnesium wire is drawn for the second time. The diameter of the copper-clad magnesium wire after the second drawing is 0.8 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 500°C and the holding time is 50 seconds.
[0083] The annealed copper-clad magnesium wire is drawn for the third time. The diameter of the copper-clad magnesium wire after the third drawing is 0.2 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 400°C and the holding time is 30 seconds.
[0084] The annealed copper-clad magnesium wire was drawn for the fourth time. The diameter of the copper-clad magnesium wire after the fourth drawing was 0.08 mm. After drawing, it was put into a vacuum annealing furnace with the temperature in the furnace set to 180° C. for 120 seconds and cooled to room temperature to obtain the copper-clad magnesium wire.
[0085] Comparative Example 1, a method for preparing a low-density and high-conductivity copper-clad magnesium conductor, comprising the following steps:
[0086] Step 1, preparing a magnesium alloy block and a copper alloy block;
[0087] The magnesium alloy block contains the following components by weight percentage: rare earth element Gd: 0.5%, and the balance is Mg and inevitable impurity elements. Pure magnesium ingots and Mg-Gd master alloys are placed in a smelting furnace by weight percentage, and the magnesium alloy is smelted under the protection of SF6 gas. After complete smelting, mechanical stirring is performed for 5 minutes, and slag is removed. A refining agent is added to the magnesium alloy molten liquid after slag removal for refining, and slag is removed again. After slag removal, the magnesium alloy is cast to obtain a magnesium alloy block. The magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 110 mm, and the obtained magnesium alloy block is homogenized. The temperature of the magnesium alloy block homogenization treatment is 450° C., and the time is 12 hours. The magnesium alloy block after homogenization needs to be surface treated to remove surface oxides.
[0088] The copper layer composition contains Mg: 0.2% by weight, and the balance is Cu and inevitable impurity elements. A pure copper block is first placed in a smelting furnace by weight, and a pure magnesium block is placed after the copper block is completely melted. After the magnesium block is completely melted, it is cast to obtain a copper alloy block, and the obtained copper alloy block is homogenized; the homogenization temperature of the copper alloy block is 850° C., and the homogenization time is 10 hours;
[0089] Step 2: Preparation and pretreatment of magnesium alloy core and copper strip;
[0090] The magnesium alloy block after homogenization is extruded to obtain a magnesium alloy core. The magnesium alloy block is extruded at a temperature of 450° C. into a round rod with a diameter of 6 mm. The obtained magnesium alloy core is pretreated to remove surface oil and oxides, and is passivated.
[0091] The copper alloy block after homogenization treatment is rolled, and the rolling process of the copper alloy block is as follows: the copper alloy block after homogenization treatment is hot rolled at 780°C, the copper alloy block is hot rolled into a plate, the hot rolling is from 30mm to 15mm, and the reduction amount for each pass is 20%, and then the hot-rolled plate is cold rolled from 15mm to 2mm, and the reduction amount for each pass is 15%; then the cold-rolled plate is heat-treated at 430°C for 4 hours; then the plate is cold-rolled from 2mm to 0.5mm, and the reduction amount for each pass is 10%; the cold-rolled plate is heat-treated at 320°C for 4 hours; a copper strip is obtained, and the obtained copper strip is pre-treated to remove surface oil and oxides, and passivation treatment is performed to increase the friction between the copper strip and the magnesium alloy core.
[0092] Step 3, welding the magnesium alloy core and the copper strip cladding;
[0093] The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device;
[0094] Then the magnesium alloy core uniformly coated with copper strip enters the welding area, and the copper-clad magnesium is welded by stir friction welding. During the stir friction welding process, the rotation speed of the stirring head is 1000rpm, the foreground speed of the stirring head is 6m / min, and the length of the stirring needle is the same as the thickness of the coated copper layer: 0.5mm; after welding, the surface is mechanically polished to make the surface smooth, and the copper-clad magnesium wire is obtained, and the diameter of the copper-clad magnesium wire is 7mm;
[0095] Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
[0096] The copper-clad magnesium wire obtained in step 3 is subjected to the first continuous drawing, and the wire diameter after the first continuous drawing is 3 mm. After drawing, it is subjected to a vacuum annealing furnace, and the temperature in the furnace is set to 500° C., and the insulation time is 50 seconds;
[0097] The annealed copper-clad magnesium wire is drawn for the second time. The diameter of the copper-clad magnesium wire after the second drawing is 0.8 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 500°C and the holding time is 50 seconds.
[0098] The annealed copper-clad magnesium wire is drawn for the third time. The diameter of the copper-clad magnesium wire after the third drawing is 0.2 mm. After drawing, it is put into a vacuum annealing furnace. The temperature in the furnace is set to 400°C and the holding time is 30 seconds.
[0099] The annealed copper-clad magnesium wire was drawn for the fourth time. The diameter of the copper-clad magnesium wire after the fourth drawing was 0.08 mm. After drawing, it was placed in a vacuum annealing furnace with the temperature in the furnace set to 400° C. for 120 seconds and cooled to room temperature to obtain the copper-clad magnesium wire.
[0100] For comparative example 2, please refer to the Chinese patent document with patent application number 202111322186.9, which discloses a process for producing copper-clad aluminum-magnesium wire using a welding cladding method. Example 1 in the patent is taken as comparative example 2 of this application.
[0101] Table 1: Comparison of composite line density, tensile strength and conductive properties of Example 1, Example 2, Example 3 and Comparative Example 1 and Comparative Example 2;
[0102]
[0103] In summary, the present invention uses friction stir welding instead of traditional argon arc welding to avoid the problem of local melting of the magnesium alloy core due to excessive local temperature in surface copper alloy welding, thereby improving the uniformity of the organization, and further adding rare earth elements to the magnesium alloy core to reduce the content of impurity elements in the magnesium alloy core, thereby promoting the initiation of non-basal slip during the drawing process, thereby improving the plasticity of the magnesium alloy core and reducing the wire breakage rate.
[0104] In addition, based on the low-temperature annealing treatment after drawing, the heavy rare earth elements in the magnesium alloy core and the Mg element in the surface copper alloy layer are segregated and clustered at crystal defects such as dislocations and grain boundaries, thereby improving the conductivity and strength of the copper-clad magnesium conductor.
[0105] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a low-density, high-conductivity copper-clad magnesium conductor, characterized in that: The copper-clad magnesium conductor comprises a magnesium alloy core and a copper layer, wherein the copper layer covers the surface of the magnesium alloy core, wherein the magnesium alloy core contains, by weight percentage, 0.5%-3% rare earth elements, and the remainder is Mg and inevitable impurity elements, and the copper layer contains, by weight percentage, 0.2%-0.5% Mg, and the remainder is Cu and inevitable impurity elements; The preparation method comprises the following steps: Step 1, preparing a magnesium alloy block and a copper alloy block; Putting pure magnesium ingots and Mg-Re master alloy into a smelting furnace according to weight percentage, smelting the magnesium alloy under the protection of SF6 gas, mechanically stirring for 3-5 minutes after complete smelting, slagging, adding refining agent to the magnesium alloy molten liquid after slagging, refining, and slagging again, casting the magnesium alloy after slagging to obtain a magnesium alloy block, and homogenizing the obtained magnesium alloy block; Firstly, a pure copper block is put into a smelting furnace according to weight percentage, and a pure magnesium block is put into the smelting furnace after the copper block is completely melted, and then the magnesium block is cast after it is completely melted to obtain a copper alloy block, and the obtained copper alloy block is homogenized; Step 2: Preparation and pretreatment of magnesium alloy core and copper strip; Extruding the homogenized magnesium alloy block to obtain a magnesium alloy core, pre-treating the obtained magnesium alloy core to remove oil stains and oxides on the surface of the magnesium alloy core, and passivating the magnesium alloy core; The copper alloy block after homogenization is rolled to obtain a copper strip, and the obtained copper strip is pretreated to remove oil and oxide on the surface of the copper strip, and the copper strip is passivated to increase the friction between the copper strip and the magnesium alloy core; The copper alloy block rolling process is as follows: the copper alloy block after homogenization is hot rolled at 780°C, the copper alloy block is hot rolled into a plate, hot rolled from 30mm to 15mm, and the reduction amount for each pass is 20%, and then the hot rolled plate is cold rolled from 15mm to 2mm, and the reduction amount for each pass is 15%; The cold rolled sheet is then heat treated at 430°C for 4-6 hours; The plate is then cold rolled from 2mm to 0.5-1mm, with a reduction of 10% per pass; After cold rolling, the plate is heat treated at 320°C for 4-6 hours; Step 3, welding the magnesium alloy core and the copper strip cladding; The copper strip and the magnesium alloy core are fed into a composite device, and the copper strip is evenly coated on the magnesium alloy core by the composite device; Then the magnesium alloy core uniformly coated with copper strips enters the welding area, and the copper-clad magnesium is welded by stir friction welding, and mechanically polished to make the surface smooth to obtain a copper-clad magnesium wire with a diameter of 4.5-7 mm; During the friction stir welding process, the stirring head rotation speed is 1000 rpm, the stirring head forward speed is 3-12 m / min, and the stirring needle length is the same as the thickness of the cladding copper layer: 0.5-1 mm; Step 4: Drawing the copper-clad magnesium wire to obtain a copper-clad magnesium conductor.
2. The method for preparing a low-density and high-conductivity copper-clad magnesium conductor according to claim 1, characterized in that: In the step 1, the magnesium alloy block is cast into a cylinder with a diameter of 80 mm and a height of 100-120 mm.
3. The method for preparing a low-density and high-conductivity copper-clad magnesium conductor according to claim 1, characterized in that: In the step 1, the temperature of the magnesium alloy block homogenization treatment is 450-500° C., and the time is 8-12 hours. The magnesium alloy block after homogenization is subjected to surface treatment to remove the surface oxide of the magnesium alloy block.
4. The method for preparing a low-density and high-conductivity copper-clad magnesium conductor according to claim 1, characterized in that: In the step 2, the magnesium alloy block is extruded at a temperature of 400° C.-450° C. and is extruded into a round rod with a diameter of 4-6 mm.
5. The method for preparing a low-density and high-conductivity copper-clad magnesium conductor according to claim 1, characterized in that: In the step 1, the homogenization temperature of the copper alloy block is 850° C.-900° C., and the homogenization time is 6-10 hours.
6. The method for preparing a low-density and high-conductivity copper-clad magnesium conductor according to claim 1, characterized in that: In the step 4, the copper-clad magnesium wire obtained in step 3 is subjected to the first continuous drawing, and the wire diameter after the first continuous drawing is 2-3 mm. After the continuous drawing, a vacuum annealing furnace is carried out, and the temperature in the furnace is set to 400° C.-500° C., and the insulation time is 30 seconds-50 seconds; The annealed copper-clad magnesium wire is subjected to a second continuous drawing, and the diameter of the copper-clad magnesium wire after the second continuous drawing is 0.8-1mm. After continuous drawing, it is placed in a vacuum annealing furnace, and the temperature in the furnace is set to 400℃-500℃, and the insulation time is 30 seconds-50 seconds; The annealed copper-clad magnesium wire is continuously drawn for the third time, and the diameter of the copper-clad magnesium wire after the third continuous drawing is 0.2-0.3 mm. After continuous drawing, it is placed in a vacuum annealing furnace, and the temperature in the furnace is set to 400°C-500°C, and the insulation time is 30 seconds-50 seconds; The annealed copper-clad magnesium wire is drawn for the fourth time, and the diameter of the copper-clad magnesium wire after the fourth drawing is 0.08-0.1 mm. After the drawing, it is put into a vacuum annealing furnace, the temperature in the furnace is set to 180°C-210°C, the insulation time is 60 seconds-120 seconds, and the copper-clad magnesium wire is cooled to room temperature to obtain the copper-clad magnesium wire.
Citation Information
Patent Citations
Copper-coated magnesium alloy wire and preparation method thereof
CN104282355A
Process for producing copper-clad aluminum-magnesium wire by using welding cladding method
CN114038628A
A metal composite material and its manufacturing method
CN102290115A